Instruments for assessing professional nursing practice environments: An integrative review - Olga Maria Pimenta Lopes Ribeiro; Corália Vicente; María Manuela Martins; Lara Vandresen; João Miguel Almeida Ventura‐Silva (2020)
ABSTRACT Objective: To identify the instruments used to evaluate the professional nursing practice environments in the hospital context. Method: An integrative review, whose research process was conducted independently by two researchers in the period from July to August 2019 in the CINHAL, PubMed and SciELO databases. Results: Based on the inclusion and exclusion criteria, 53 studies published between 2009 and 2019 were considered for analysis. Ten instruments and three thematic areas were identified: instruments for the assessment of the nursing professional practice environments; implications of the use of instruments for the assessment of nursing professional practice environments; limitations of the instruments for the assessment of nursing professional practice environments. Conclusion: Despite the relevance of the instruments identified, this integrative review provides contributions that support the need to use specific tools to assess the nursing practice environments that include the structure, process and outcome components.